The Representation of Gender Roles in Pinter’s Plays Birthday Party and Old Times - Abdelhamid, Faiza (My University, 2017)
This dissertation tends to demonstrate two different plays of the British playwright Harold Pinter, Birthday Party (1958) and Old Times (1970) from the gender perspective which is apparent throughout the characters performance and the depiction of male and female behaviors from social and psychological view. The work is based on Judith butler’s theory of ‘Gender Performativity’, throughout Pinter’s representation of his characters. The first chapter introduces an overview about Pinter’s life and work; also it represents some definitions about gender concepts concerning the selected work. Literary critics have examined the characters’ performance and their issues; after the war, and the impact of the social and political transformations in the British society through the second chapter Birthday Party, the examination of gender changes appears on both masculine and feminine figure that they expressed their fear and anxiety from the outside and the conflict between them, also it exposes women’s life under a patriarchal society who lived under oppression and male’s subjugation. For the third chapter Old Times shows the psychological struggle and the sex war between characters by recovering their memories, the examination of male figure fighting for their own power and authority through sexuality. However, the representation of women’s emergence after the war, and their capabilities to become dominant and powerful.
Keywords: British literature; Play; Gender role analysis; Harold Pinter's Birthday Party (1958), Old Times (1970; Gender behavior; Sociological; Psychological; Analysis and critics